2015
DOI: 10.1136/heartjnl-2014-307220
|View full text |Cite
|
Sign up to set email alerts
|

Culprit or multivessel revascularisation in ST-elevation myocardial infarction with cardiogenic shock

Abstract: This study showed that, compared with culprit vessel revascularisation, multivessel revascularisation at the time of primary PCI was associated with better outcomes in patients with STEMI with cardiogenic shock. Our results support the current guidelines regarding revascularisation in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 20 publications
2
32
0
2
Order By: Relevance
“…This data is gathered from a large prospective multicentre registry in Korea with substantial volume and experienced PCI facilities and provides a number of important findings. First, similar to other registry data and despite the clear guideline recommendations, less than 25% of the patients with STEMI with MVD and cardiogenic shock were revascularised 8 9. Second, although both study arms were well matched and evenly distributed, the results demonstrate the challenges of interpreting registry data with clearly different conclusions based on adjusted versus unadjusted rates.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…This data is gathered from a large prospective multicentre registry in Korea with substantial volume and experienced PCI facilities and provides a number of important findings. First, similar to other registry data and despite the clear guideline recommendations, less than 25% of the patients with STEMI with MVD and cardiogenic shock were revascularised 8 9. Second, although both study arms were well matched and evenly distributed, the results demonstrate the challenges of interpreting registry data with clearly different conclusions based on adjusted versus unadjusted rates.…”
supporting
confidence: 68%
“…In a recent Heart paper, investigators from the Korean Acute Myocardial Infarction Registry (KAMIR), report outcomes of 510 patients with STEMI with cardiogenic shock and MVD, comparing 386 patients who received ‘culprit only’ PCI with 124 patients receiving multivessel PCI 8. The unadjusted MACE rate, (all-cause death, recurrent MI, any revascularisation) did not differ between groups.…”
mentioning
confidence: 99%
“…176 Some observational studies have reported potential benefits with multivessel PCI in CS, whereas clinical practice guidelines recommend nonculprit PCI for "critical (≥90% diameter) stenoses or highly unstable lesions." 145,[177][178][179][180][181] The CULPRIT-SHOCK trial (Culprit Lesion Only PCI Versus Multivessel PCI in Cardiogenic Shock), designed to be the largest CS trial ever, is currently enrolling patients to test this question in a prospective, randomized fashion. Historically, diagnostic angiography and PCI have been performed with a femoral arterial access site, although radial access has been more recently advocated as a safer alternative for arterial access.…”
Section: Pci Strategymentioning
confidence: 99%
“…It is important to note that a recent study reported significantly better outcomes in cases of multivessel revascularization as compared with revascularization of the culprit lesion alone in patients with cardiogenic shock [10]. Another study showed that in STEMI patients with cardiogenic shock and cardiac arrest, multi-vessel revascularization during primary PCI significantly improved the clinical outcome and survival rate [11].…”
Section: Discussionmentioning
confidence: 99%